2019
DOI: 10.14309/ctg.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Prostate-Specific Membrane Antigen in Tumor-Associated Vasculature Predicts Poor Prognosis in Hepatocellular Carcinoma

Abstract: INTRODUCTION: Prostate-specific membrane antigen (PSMA) was originally found to be specifically expressed in normal prostate, and its expression was upregulated in almost all stages of prostate cancer. In recent years, PSMA was also found to be expressed in tumor-associated vasculature in many nonprostatic solid tumors. However, the expression pattern of PSMA in hepatocellular carcinoma (HCC) is not well studied. METHODS: In this study, we examined PSMA expression in 103 HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 33 publications
4
72
1
Order By: Relevance
“…Tumor parenchyma staining was positive in a majority of NSCLC samples (54 of 80), which is consistent with previous reports of anxA1 expression in lung tumors [37][38][39][40]. Although induction of anxA1 expression in lung tumor vasculature was not as prevalent and widespread as that seen in other tumor vascular targets, notably B7-H3 [8] and PSMA [65,66], these data validate anxA1 as a potential tumor vascular drug target in a proportion of human lung tumors.…”
Section: Plos Onesupporting
confidence: 89%
“…Tumor parenchyma staining was positive in a majority of NSCLC samples (54 of 80), which is consistent with previous reports of anxA1 expression in lung tumors [37][38][39][40]. Although induction of anxA1 expression in lung tumor vasculature was not as prevalent and widespread as that seen in other tumor vascular targets, notably B7-H3 [8] and PSMA [65,66], these data validate anxA1 as a potential tumor vascular drug target in a proportion of human lung tumors.…”
Section: Plos Onesupporting
confidence: 89%
“…Importantly, patients with disease recurrence in our study had longer history of disease after TACE. A previously published limited immunohistochemistry study showed that 74-80% of HCC tumors presented moderate-to-strong staining for PSMA, while completely negative staining was seen in only 4-26% of samples [11,19]. All studies showed PSMA expression in the neovascular structures [11,12,19].…”
Section: Discussionmentioning
confidence: 74%
“…However, as liver gluconeogenesis in well-differentiated HCC is comparable to normal, the sensitivity of [ 18 F]FDG PET for detecting HCC is not better than that of conventional imaging (50-70%) [2]. Therefore, other PET tracers based on lipid metabolism have been proposed for the detection of HCC, including [ 11 [3,2]. Similarly, [ 18 F]F-choline (which is a component of phosphatidylcholine, an essential element in cell membranes) has a similar sensitivity to [ 11 C]C-labeled acetate, ranging from 75 to 87% [3,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most patients with HCC are diagnosed during the middle and advanced stages, during which traditional radiotherapy and chemotherapy have limited clinical benefit. This is primarily due to high rates of recurrence and metastasis (4), therefore, it is important to identify novel diagnostic and prognostic markers to aid earlier intervention.…”
Section: Introductionmentioning
confidence: 99%